1997
DOI: 10.1046/j.1365-2567.1997.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively activated macrophages actively inhibit proliferation of peripheral blood lymphocytes and CD4+ T cells in vitro

Abstract: SUMMARYWe compared the immunological functions of interferon-c (IFN-c)-induced, classically activated macrophages (caMW) and of interleukin-4 (IL-4)-and glucocorticoid-induced, alternatively activated macrophages (aaMW) in a human co-culture system in vitro. Proliferation of peripheral blood leucocytes (PBL) or CD4+ T cells mediated by optimal doses of phytohaemagglutinin (PHA) or concanavalin A (Con A) was only marginally influenced by caMW, but was strongly inhibited by aaMW. The degree of lymphocyte prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 63 publications
3
82
0
2
Order By: Relevance
“…M2 cells are considered to induce Th2 differentiation of CD4 ϩ T cells and cause Th1 tolerance (38,51,69). They may have potential roles in immune suppression (34,62). Loke et al (34) reported that the IL-4-induced alternatively activated macrophages reversibly inhibited T cell proliferation by a cell-to-cell contact mechanism, similar to the suppression we observed in tumor progressors.…”
Section: Discussionsupporting
confidence: 72%
“…M2 cells are considered to induce Th2 differentiation of CD4 ϩ T cells and cause Th1 tolerance (38,51,69). They may have potential roles in immune suppression (34,62). Loke et al (34) reported that the IL-4-induced alternatively activated macrophages reversibly inhibited T cell proliferation by a cell-to-cell contact mechanism, similar to the suppression we observed in tumor progressors.…”
Section: Discussionsupporting
confidence: 72%
“…Functionally, they can induce tolerance and down-regulate inflammatory responses (28). In one report, IL-4-stimulated human macrophages inhibited mitogen-mediated proliferation of CD4 ϩ lymphocytes by an as yet unknown mechanism (29). Our experiments suggest a relationship between our myeloid suppressors and the alternatively activated macrophages, particularly in the case of MSC-2, which not only gains the suppressive phenotype in response to IL-4 (Figs.…”
Section: Discussionsupporting
confidence: 53%
“…I g is produced by T cells upon cue from I 12 and MHC displayed on the membrane of C. A inhibits production of I g by T cells (7). Including an I g decay term gives the following:…”
Section: Resultsmentioning
confidence: 99%
“…Martinez and colleagues also refer to these as M1 macrophages, characterizing them as having elevated expression of MHC-II, CD80, and CD86 costimulatory molecules and promoting TH1 differentiation and IFN-␥ production by T cells via the production of IL-12 (4). A different, more recently studied class of macrophages, is known as alternatively activated macrophages (AAM) (2,(5)(6)(7)(8). Also referred to as M2a macrophages, these macrophages have a phenotype resembling macrophages activated by Interleukin-4 (IL-4) or IL-13 and are characterized by the up-regulation of scavenger receptors and the mannose receptor.…”
mentioning
confidence: 99%